EFFECT OF ROLL BENDING FORCE ON HOT ROLLING FORMING OF Q345R/316L STAINLESS STEEL CLAD PLATE - JIN HeRong; DAI Chao; HAN MinFeng (Jixie qiangdu)
Aimed at the presetting problems of the roll bending force during vacuum hot rolling of Q345 R/316 L stainless steel clad plates, a three dimensional thermo-mechanical finite element model of rolling for stainless steel clad plates was proposed by using the FE software MSC.MARC. Four boundary conditions of model bending roll force are set 0 kN, 300 kN, 500 kN and 800 kN respectively. The distribution law of reduction of the base plate, the bending deformation of the roll system and semi-loaded roll gap in the width direction of the clad plate under different bending roll forces were studied by numerical simulation. The distribution law of interfacial stress and strain under different bending roll forces was analyzed. According to the judgment condition of interface bonding condition, the optimum bending force was set. The simulation results show that the shape of plate appears high in the middle and low at the edge without bending force. When the roll bending force is applied, the shape of plate is obviously improved, and the optimum setting value of the bending force is 500 kN. Under the condition that the total deformation is constant, the increase of bending force will promote the deformation of the base metal and the cladding metal. Thus uniform stress-strain distribution and good coordinating deformation can be realized, which is beneficial to the interfacial bonding of clad plates.